Increasing the order parameter of quasi-hexagonal micellar nanostructures by ultrasound annealing - Williges, Christian; Chen, Wenwen; Morhard, Christoph; Spatz, Joachim P.; Brunner, Robert (Langmuir, 2013)
Nanopatterning with block copolymers finds many applications ranging from optics to bioscience. Many of these uses demand highly ordered patterns that are difficult to obtain because of environmental influences during fabrication. Here we demonstrate that ultrasonication improves the hexagonal order of artificially disturbed micellar nanopatterns.
Gesehen am 15.11.2021